1994
DOI: 10.1161/01.hyp.24.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional hemodynamic effects of corticotropin in conscious sheep.

Abstract: The regional hemodynamic effects of 5 days of intravenous infusion of corticotropin (ACTH) (5 /xg/kg per day) were examined in conscious sheep (n=8). Mean arterial pressure increased from 81 ±2 to 93±3 mm Hg (/><.001) on day 2 of ACTH and remained at this level during the infusion. Cardiac output increased from 5.13±0.19 to 6.06±0.33 L/min (/ ) <.O1) because of an increase in stroke volume from 65±4 to 79±8 mL per beat (P<.01); heart rate remained unchanged. ACTH did not alter total peripheral conductance but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…This type of hypertension, which is dependent on increased CO, is similar to that found with cortisol-and corticotropin (' ACTH ')-induced hypertension in humans and sheep [17,[19][20][21][22][23]. In addition, the increase in CO was due to an increase in stroke volume, not in HR.…”
Section: Discussionsupporting
confidence: 78%
“…This type of hypertension, which is dependent on increased CO, is similar to that found with cortisol-and corticotropin (' ACTH ')-induced hypertension in humans and sheep [17,[19][20][21][22][23]. In addition, the increase in CO was due to an increase in stroke volume, not in HR.…”
Section: Discussionsupporting
confidence: 78%
“…The increase in stroke volume could result from an increase in ventricular contractility due to cardiac hypertrophy, or from an increased preload (increase in plasma volume). This type of hypertension, which is dependent on increased CO, is similar to that found with cortisol-and corticotropin (' ACTH ')-induced hypertension in humans and sheep [17,[19][20][21][22][23]. This raises the possibility that prenatal dexamethasone could have altered permanently the level of one or more steroids, or of their receptors, which would ultimately lead to hypertension.…”
Section: Discussionsupporting
confidence: 69%
“…β‐Adrenoceptor blockade did not prevent the rise in cardiac output or the rise in blood pressure, 37 but both nisoldipine and minoxidil prevented the development of the increase in blood pressure 30 . Subsequent studies confirmed these changes (rise in cardiac output, no change in total peripheral conductance) 38 . The unchanged total peripheral conductance reflected regional alterations, with falls in mesenteric and iliac conductances and a rise in renal conductance 38 consistent with increased mesenteric and iliac resistances and decreased renal resistance.…”
Section: Haemodynamic Consequences Of Acth Administrationmentioning
confidence: 96%